2021
DOI: 10.1021/acsestwater.1c00293
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Manganese Occurrence in Drinking Water in the United States

Abstract: The United States Environmental Protection Agency (USEPA) Unregulated Contaminant Monitoring Rule (UCMR) requires the nationwide monitoring of drinking water for specific unregulated contaminants. In the recent (2018−2020) fourth round (UCMR 4), more than 37 000 samples from over 5000 water systems (4200 large and 800 small) were analyzed for manganese. USEPA developed (2004) a 300 μg/L health advisory limit, but both Health Canada (2020) and the World Health Organization ( 2021) have recently reevaluated the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 6 publications
1
15
0
Order By: Relevance
“…Dissolved manganese is widely found in both surface water and groundwater at concentrations ranging from a microgram per liter to several milligrams per liter. 1,2 Because of the health and organoleptic impacts of Mn, the removal of Mn from raw water is often a necessary task for water treatment plants (WTPs). 3−5 While particulate Mn can be easily separated from water by sedimentation and filtration processes, dissolved Mn(II) removal is more challenging.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dissolved manganese is widely found in both surface water and groundwater at concentrations ranging from a microgram per liter to several milligrams per liter. 1,2 Because of the health and organoleptic impacts of Mn, the removal of Mn from raw water is often a necessary task for water treatment plants (WTPs). 3−5 While particulate Mn can be easily separated from water by sedimentation and filtration processes, dissolved Mn(II) removal is more challenging.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Dissolved manganese is widely found in both surface water and groundwater at concentrations ranging from a microgram per liter to several milligrams per liter. , Because of the health and organoleptic impacts of Mn, the removal of Mn from raw water is often a necessary task for water treatment plants (WTPs). While particulate Mn can be easily separated from water by sedimentation and filtration processes, dissolved Mn­(II) removal is more challenging. , Mn­(II) oxidation to Mn oxides (MnO x ) through chemical or biological pathways is crucial for Mn­(II) removal. Residual Mn­(II) in finished water can undergo further oxidation to produce MnO x during distribution processes and form Mn deposits on the inner surfaces of pipes. ,, MnO x can stain laundry, dishes, and toilets, cause a visible color, and increase the turbidity of drinking water, leading to customer complaints. …”
Section: Introductionmentioning
confidence: 99%
“…Additionally, 8.7% were found to exceed the proposed WHO guideline of 80 μg/L, 6% exceeded the Health Canada Maximum Acceptable Concentration of 120 μg/L, and 2.1% exceeded the USEPA Health Advisory Level of 300 μg/L. Following the results of UCMR 4, USEPA has included Mn in the UCMR 5 for systems serving 3001-10,000 to improve understanding of national occurrence of Mn in drinking water (Eaton, 2021). A recent survey of groundwater wells conducted in Manitoba, Canada found that approximately 34% of tested wells were above the 2019 Canadian health-based guideline of 120 μg/L (Government of Manitoba, 2021).…”
Section: Article Impact Statementmentioning
confidence: 99%
“…Manganese (Mn) is a naturally occurring, redox-active mineral ubiquitous in soils, and sediments globally. Its release into groundwater is primarily due to microbially-mediated reductive dissolution of naturally occurring minerals controlled by local biogeochemical conditions. In surface waters, seasonal redox stratification can result in anoxic conditions favorable for the release of Mn in surface water; , however, previous studies of Mn occurrence in surface and groundwater have demonstrated higher rates of exceedances in groundwater sources in the United States . Although less common, Mn from anthropogenic sources, such as industrial or mining activities, can be released into the environment or exacerbate its geochemical release. , …”
Section: Introductionmentioning
confidence: 99%